Developmental Refusal and Farmers’ Vulnerabilities in Central Kalimantan Peatlands - Pujo Semedi; Rio Heykhal Belvage (Lembaran Antropologi, 2025)
The conversion of peatlands in Central Kalimantan into an intensive food crop production area places farmers in a vulnerable position. Their clear vulnerability stems from their reliance on the market and their exposure to harmful agricultural chemicals. Additionally, government policies promoting the migration of farmers into the peatlands, based on the assumption that local farmers lack the capacity to improve their own circumstances, have created social tension. This research draws on fieldwork and participant observation to analyze the statements of Kalampangan’s local farmers and their demand for land reclamation. In addition, this research also incorporates various online sources, including local and national newspapers, government agencies, journals, and personal blogs. The findings suggest that local farmers are active participants in development who intentionally challenge the government’s negative assessment. Through their demands for fairness and their rejection of state-defined notions of progress, local farmers assert their own values and lived experiences as the basis for defining what “development” should mean.